College Students' Knowledge Concerning Oropharyngeal Cancer, Human Papillomavirus, and Intent Toward Being Examined. Issue 3 (July 2018) - Walker, Kimberly; Jackson, Richard
Abstract : The purpose of this study was to assess college students' knowledge of oral/oropharyngeal cancer and the relationship of human papillomavirus (HPV) to oropharyngeal cancer. Data were also collected to determine their perceived susceptibility to oropharyngeal cancer and awareness of emotions toward and intentions to receive an oral cancer examination in order to design tailored messages for promoting oropharyngeal cancer prevention on college campuses. Two hundred ten baccalaureate students in nonhealth majors from a public southeastern university were surveyed. Descriptive statistics were calculated, and multiple regression analysis was conducted to determine the predictors of knowledge of oral/oropharyngeal cancer and the HPV and intentions to be examined. Results indicated most were unaware of oropharyngeal cancer, did not understand the purpose of an oral cancer examination, and could not affirm they had received one or had one explained to them. Results also indicated poor understanding of some of the signs and risk factors of oropharyngeal cancer, especially HPV. In addition, oral/oropharyngeal cancer knowledge and negative emotions were predictors of examination intentions, confirming current behavioral theories that postulate rational decisions require collaboration from both cognitive and affective systems. Recommendations are offered for tailored educational communications and strategies about oropharyngeal cancer on college campuses.